2021
DOI: 10.1186/s40709-021-00151-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FBXL19-AS1 promotes proliferation and metastasis of cervical cancer through upregulating COL1A1 as a sponge of miR-193a-5p

Abstract: Background Cervical cancer (CC) is one of the most common and malignant tumors in women. In this study, we aim to explore the role and mechanism of F-box and leucine rich repeat protein 19 antisense RNA 1 (FBXL19-AS1), a novel long-chain non coding RNA (lncRNA) with marked roles in a variety of tumors, in regulating the proliferation and metastasis of CC. Methods The expression of FBXL19-AS1, miR-193a-5p and COL1A1 were detected by RT-PCR and weste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 48 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Moreover, it has been reported that lncRNA FBXL19-AS1 regulates invasion, migration, and growth of cervical cancer by miR-193a-5p/PIN1 axis [23]. lncRNA FBXL19-AS1 enhances metastasis and proliferation by miR-193a-5p/ COL1A1 axis in cervical cancer [24]. e depletion of SFRS9 represses colorectal cancer progression by enhancing ferroptosis by GPX4 [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that lncRNA FBXL19-AS1 regulates invasion, migration, and growth of cervical cancer by miR-193a-5p/PIN1 axis [23]. lncRNA FBXL19-AS1 enhances metastasis and proliferation by miR-193a-5p/ COL1A1 axis in cervical cancer [24]. e depletion of SFRS9 represses colorectal cancer progression by enhancing ferroptosis by GPX4 [25].…”
Section: Discussionmentioning
confidence: 99%
“…e function of circACAP2 in the regulation of other types of programmed cell death such as apoptosis and pyroptosis should be validated in future investigations. Meanwhile, it has been identified that miR-193a-5p plays a critical role in the development of cervical cancer [23,24], and we identified the potential interaction between circACAP2 and miR-193a-5p in the bioinformatic analysis. However, as we all know, circRNAs target multiple downstream miRNAs and other miRNAs sponged by circACAP2 need to be identified in cervical cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Culture of cells was in Roswell Park Memorial Institute (RPMI) 1640 (Gibco, NY, USA) medium covering 10% fetal bovine serum (FBS) (Gibco, NY, USA) and 1% penicillin/streptomycin (Gibco, NY, USA). Selection of Hela cells is as the auxiliary research object owing to its extremely elevated difference [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Presently, the critical clinical treatment strategies for CC cover surgery, chemotherapy, and radiotherapy. Nevertheless, radiotherapy and chemotherapy are available to kill a considerable number of normal cells owing to the limitation of the adaptation stage of surgical cure [ 2 ]. Nevertheless, these traditional therapy methods are unable to effectively cure CC, and infiltration, metastasis, and recurrence remain the crucial reason of death [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation